2005
DOI: 10.2174/1568006054064799
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Mediated Rejection in Pig-To-Nonhuman Primate Xenotransplantation Models

Abstract: Antibody-mediated mechanisms are central to the rejection that occurs when pig organs are transplanted into primates. In this article, the histopathological features of the humoral rejection process in these species combinations, namely hyperacute rejection and acute humoral xenograft rejection, will be illustrated. The profile of the natural and elicited antibodies involved will also be discussed. It has now been demonstrated that the natural immune response to a porcine xenograft is primarily directed to Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 201 publications
(301 reference statements)
0
12
0
Order By: Relevance
“…Several lines of evidence support the importance of both anti-aGal and anti-non-aGal antibodies in the establishment of AHXR (as reviewed by Cozzi et al, 2005). In particular, the relevance of anti-non-aGal immunoglobulins has recently been demonstrated in a study by Kuwaki and colleagues (Kuwaki et al, 2005) where AHXR was observed in 5/8 cases of heterotopic aGalT j/j pig heart transplantation to baboons.…”
Section: Acute Humoral Xenograft Rejectionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several lines of evidence support the importance of both anti-aGal and anti-non-aGal antibodies in the establishment of AHXR (as reviewed by Cozzi et al, 2005). In particular, the relevance of anti-non-aGal immunoglobulins has recently been demonstrated in a study by Kuwaki and colleagues (Kuwaki et al, 2005) where AHXR was observed in 5/8 cases of heterotopic aGalT j/j pig heart transplantation to baboons.…”
Section: Acute Humoral Xenograft Rejectionmentioning
confidence: 84%
“…The removal of XNA has been achieved by ex vivo serum perfusion, plasmapheresis, and XNA neutralisation, (reviewed in Cozzi et al, 2005). Similarly, advancements in cloning strategies in large animal models have recently allowed the development of genetically modified pigs lacking the galactosyltransferase gene (aGalT j/j ), and hence aGal epitopes (Lai et al, 2002).…”
Section: Strategies To Overcome the Immunological Barriersmentioning
confidence: 99%
“…The pathogenic mechanism of early (hyperacute rejection) and delayed humoral xenograft rejection (acute vascular rejection, also called acute humoral xenograft rejection) includes a distortion of endothelial shape caused by the binding of antibodies to the endothelium and activation of the complement cascade (3). Activation and change of the endothelial cell lining mediates the change from an anticoagulant to a procoagulant state, and allows the immediate interaction of circulating platelets with the matrix underlying the endothelial cells, resulting in platelet activation and aggregation (4,5).…”
mentioning
confidence: 99%
“…During the period, May to June 2005, six reviews on xenotransplantation were published [1][2][3][4][5][6]. Vodicka et al [1] discussed the use of the miniature pig as a model in biomedical research.…”
mentioning
confidence: 99%
“…Cozzi et al [5] summarized the role of antibodies in the rejection process of pig-to-non-human primate xenografts. The authors discussed the pathophysiology of hyperacute xenograft rejection and acute humoral xenograft rejection, and illustrated different strategies that had been attempted to prevent the onset of antibody-mediated rejection.…”
mentioning
confidence: 99%